2019
DOI: 10.3892/etm.2019.7887
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV inhibits excessive mesangial cell proliferation and renal fibrosis caused by diabetic nephropathy via modulation of the TGF‑β1/Smad/miR‑192 signaling pathway

Abstract: Astragaloside IV (ASI) exhibits a wide variety of pharmacological effects in cardiovascular diseases, hepatitis and kidney disease and due to this, ASI has recently become an attractive research target. The present study aimed to determine the effect of ASI on renal fibrosis and the mechanisms underlying its therapeutic effects in diabetic nephropathy (DN). In vitro, ASI was added to rat mesangial cells (RMCs) and cultured with a high level of glucose (HG) to observe the effects exhibited on proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Fortunately, some of the compounds purified from the six herbs of GSJD have been used to treat DN and gained satisfactory results. For instance, astragaloside IV 26,[40][41][42][43][44][45][46] , berberine 39,[47][48][49][50][51] , emodin 38,52 and rhein 53,54 could ameliorate DN by modulating multiple signalling pathways. Therefore, further investigation of the active compounds in GSJD is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, some of the compounds purified from the six herbs of GSJD have been used to treat DN and gained satisfactory results. For instance, astragaloside IV 26,[40][41][42][43][44][45][46] , berberine 39,[47][48][49][50][51] , emodin 38,52 and rhein 53,54 could ameliorate DN by modulating multiple signalling pathways. Therefore, further investigation of the active compounds in GSJD is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-370, which is highly increased in the renal DN model, is capable of triggering cell proliferation by targeting canopy 1 (CNPY1) [28]. On the other hand, level of miR-192 is reported to be elevated in high glucose-treated rat MCs, and it regulates MC proliferation and renal fibrosis [59]. Moreover, a recent study showed that miR-379-5p has a critical role in renal fibrosis during DN.…”
Section: Role Of Mirnas In Cell Proliferation In Dnmentioning
confidence: 99%
“…The pathogenesis of DN is related to the excessive proliferation and fibrosis of mesangial cells (MCs) [31]. Several lncRNAs have been proved to contribute to regulate MCs proliferation and fibrosis in vivo and in vitro.…”
Section: Lncrnas Associate With Glomerular Injurymentioning
confidence: 99%